2018
DOI: 10.4067/s1726-569x2018000100095
|View full text |Cite
|
Sign up to set email alerts
|

Gifts and Conflicts of Interest: In Shades of Gray?

Abstract: Gifts are a regular practice within the relationships established by business world stakeholders with the professionals that may be instrumental in promoting their sales. Consequently, gifts are a potential source of conflicts of interest. This article is the result of a bibliographic study of papers addressing gifts, published in scientific journals which was carried out with the aim of identifying what kinds of professions address the issue and in what ways, in order to reach conclusions that may enhance ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Selling unneeded pharmaceuticals to pharmacies, presenting drug baskets, selling drugs with presents, and inappropriate drug distribution among community pharmacies are all examples of the unethical activities observed within drug distribution businesses. Because of these issues, pharmacists sometimes overlook product quality, which impacts their professional conduct and decision-making [18].…”
Section: Regulations and Policies-related Issuesmentioning
confidence: 99%
“…Selling unneeded pharmaceuticals to pharmacies, presenting drug baskets, selling drugs with presents, and inappropriate drug distribution among community pharmacies are all examples of the unethical activities observed within drug distribution businesses. Because of these issues, pharmacists sometimes overlook product quality, which impacts their professional conduct and decision-making [18].…”
Section: Regulations and Policies-related Issuesmentioning
confidence: 99%
“…A bibliography study by Volochinsky et al (2018) concluded that conflicts of interest produced by gift giving result in an 'undeniable dependence on relationships that implicitly lead to reciprocity and deprive the professionals from the necessary autonomy and impartiality' (p. 101). But there is another side to this story as well.…”
Section: Giftsmentioning
confidence: 99%